Answer:
A
Step-by-step explanation:
Answer:
5 ft
Step-by-step explanation:
Let the height of the previous jump be represented by j. Then 1.1j = 5.5 ft.
Dividing both sides by 1.1, we get j = 5 ft. This was the height of the previous jump.
Answer:
![\large \boxed{2}](https://tex.z-dn.net/?f=%5Clarge%20%5Cboxed%7B2%7D)
Step-by-step explanation:
The formula for the nth term of a geometric sequence is
aₙ = a₁rⁿ⁻¹
In your geometric sequence, a₁ = 4 and a₁₃ = 16 384.
![\begin{array}{rcl}16384 & = & 4r^{(13 - 1)}}\\16384 & = & 4r^{12}\\4096 & = & r^{12}\\3.6124 & = & 12 \log r\\0.30102 & = & \log r\\r & = & 10^{0.30102}\\ & = & \mathbf{2}\\\end{array}\\\text{The common ratio is $\large \boxed{\mathbf{2}}$}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Brcl%7D16384%20%26%20%3D%20%26%204r%5E%7B%2813%20-%201%29%7D%7D%5C%5C16384%20%26%20%3D%20%26%204r%5E%7B12%7D%5C%5C4096%20%26%20%3D%20%26%20r%5E%7B12%7D%5C%5C3.6124%20%26%20%3D%20%26%2012%20%5Clog%20r%5C%5C0.30102%20%26%20%3D%20%26%20%5Clog%20r%5C%5Cr%20%26%20%3D%20%26%2010%5E%7B0.30102%7D%5C%5C%20%26%20%3D%20%26%20%5Cmathbf%7B2%7D%5C%5C%5Cend%7Barray%7D%5C%5C%5Ctext%7BThe%20common%20ratio%20is%20%24%5Clarge%20%5Cboxed%7B%5Cmathbf%7B2%7D%7D%24%7D)
Check:
![\begin{array}{rcl}16384 & = & 4(2)^{12}\\16384 & = & 4(4096)\\16384 & = & 16384\\\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Brcl%7D16384%20%26%20%3D%20%26%204%282%29%5E%7B12%7D%5C%5C16384%20%26%20%3D%20%26%204%284096%29%5C%5C16384%20%26%20%3D%20%26%2016384%5C%5C%5Cend%7Barray%7D)
It checks.
Answer:
The inductive reasoning is based on A: a limited number of observations
Step-by-step explanation:
Let's say you lived until 90 years old, and took a observation on July 4th each year. Even if you lived until 90 years old, you would only have 90 observations. And inductive reasoning allows for statements to be false, so any of the 90 observations that you took can be proven false. So really, you would have only 90 observations, with any of them that could be false. A limited number of observations would be the only thing that you could base this reasoning off of.
Answer:
<u>$173,954.01</u>
Step-by-step explanation:
Finding compound interest :
- A = (150,000)(1 + 0.025)⁶
- A = (150,000)(1.025)⁶
- A = (150,000)(1.15969342)
- A = <u>$173,954.01</u>